PEMANFAATAN SIM PADA MANAJEMEN HUBUNGAN SEKOLAH DAN MASYARAKAT DI KOTA KEFAMENANU - Bernadus Ghawa Rado; Emilia Khristina Kiha (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This descriptive qualitative study has three research focuses, namely (1) What is the school background in organizing a school website at Kefamenanu 1 Public Middle School and Putri St. Junior High School. Xaverius Kefamenanu, (2) How are the steps to use the School website as a Public Relations Facility at Kefamenanu 1 Public Middle School and Putri St. Middle School. Xaverius Kefamenanu and (3) How is the management of SIM management in order to support the function of Husemas activities at Kefamenanu 1 Public Middle School and Putri St. Junior High School. Xaverius Kefamenanu. The fourth finding is that of SMP 1 Kefamenanu and Putri St. Junior High School. Xaverius Kefamenanu has similarities in the form of: (a) attitude towards competition, (b) ideals of using school websites for e-learning media, (c) general content and packaging messages on school websites, (d) the information processing mechanism is not yet implemented , (e) opportunities for workers to attend training. For the differences themselves: (a) availability of human resources with relevant formal education background, (b) availability of supporting facilities and funds, (c) relationship between public relations function and website manager, (d) principal evaluation style, (e) renewal data, (f) variations in the content of information on the website, (g) availability of compensation for managers of school websites, and (h) the role of school principals in administering the website